Signal propagation analysis for low data rate wireless sensor network applications in sport grounds and on roads - Ndzi, David L.; Muhammad A, Mohd Arif; Ali Yeon, Md Shakaff, Prof. Dr.; Mohd Noor, Ahmad, Prof. Dr.; Azizi, Harun; Latifah Munirah, Kamarudin; Ammar, Zakaria; M. F., Ramli; Mohammad Shahrazel, Razalli (EMW Publishing, 2013)
Link to publisher's homepage at http://www.emacademy.org/